2011
DOI: 10.1103/physreva.83.023405
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of oriented carbonyl sulfide molecules by intense circularly polarized laser pulses

Abstract: We present combined experimental and theoretical results on strong-field ionization of oriented carbonyl sulfide molecules by circularly polarized laser pulses. The obtained molecular frame photoelectron angular distributions show pronounced asymmetries perpendicular to the direction of the molecular electric dipole moment. These findings are explained by a tunneling model invoking the laser-induced Stark shifts associated with the dipoles and polarizabilities of the molecule and its unrelaxed cation. The focu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 64 publications
(109 reference statements)
6
56
0
Order By: Relevance
“…There is currently a strong interest in the elucidation of this question. For example in the OCS molecule, experiments with circularly polarized light and theory show that ionization occurs most readily from the O-end, i.e., when the field points towards the Send [85][86][87]. For linearly polarized light, on the other hand, one experiment reports most ionization from the Send [88], while another most perpendicular to the molecular axis [89].…”
Section: Strong-field Ionizationmentioning
confidence: 99%
“…There is currently a strong interest in the elucidation of this question. For example in the OCS molecule, experiments with circularly polarized light and theory show that ionization occurs most readily from the O-end, i.e., when the field points towards the Send [85][86][87]. For linearly polarized light, on the other hand, one experiment reports most ionization from the Send [88], while another most perpendicular to the molecular axis [89].…”
Section: Strong-field Ionizationmentioning
confidence: 99%
“…In Ref. [23], we modified the tunneling model to include the Stark shifts of the molecule and its cation at the instantaneous value of the external field. We briefly summarize the model here for completeness.…”
Section: Theory a Stark-shift Corrected Tunneling Theorymentioning
confidence: 99%
“…This molecule has been examined by several research groups using different methods. [26][27][28][29][30][31] According to the most elementary theories, the SFI rate is expected to be largest when the electron is removed via the S atom where the density of the HOMO is maximal. However, Holmegaard et al 26 showed experimentally that for circularly polarized laser pulses with a peak intensity of ≈ 2.4 × 10 14 W/cm 2 the ionization of OCS is enhanced when the field points from the O to the S atom.…”
Section: Introductionmentioning
confidence: 99%